2017
DOI: 10.1007/s00726-017-2435-0
|View full text |Cite
|
Sign up to set email alerts
|

Functions of pregnane X receptor in self-detoxification

Abstract: Pregnane X receptor (PXR, NR1I2), a member of the nuclear receptor superfamily, is a crucial regulator of nutrient metabolism and metabolic detoxification such as metabolic syndrome, xenobiotic metabolism, inflammatory responses, glucose, cholesterol and lipid metabolism, and endocrine homeostasis. Notably, much experimental and clinical evidence show that PXR senses xenobiotics and triggers the detoxification response to prevent diseases such as diabetes, obesity, intestinal inflammatory diseases and liver fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Chen et al reported that AKG intervention in mice reduces body weight and affects the intestinal innate immunity via alterations of gut microbiota [20]. It is interesting that studies have also identified that AKG treatment can inhibit the NF- κ B-mediated inflammatory pathway, thereby enhancing gut immunity and promoting self-detoxification systems [29, 33]. It has also been validated that AKG intervention can enhance the expression of inflammatory cytokines [29].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that AKG intervention in mice reduces body weight and affects the intestinal innate immunity via alterations of gut microbiota [20]. It is interesting that studies have also identified that AKG treatment can inhibit the NF- κ B-mediated inflammatory pathway, thereby enhancing gut immunity and promoting self-detoxification systems [29, 33]. It has also been validated that AKG intervention can enhance the expression of inflammatory cytokines [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al (2015) reported that AKG lowered body weight and affected intestinal innate immunity through influencing intestinal microbiota in mice [ 27 ]. Of note, our group also found that AKG could suppress NF-κB-mediated inflammatory pathway and enhance the PXR-regulated detoxification pathway to improve intestinal immune and self-detoxification system [ 24 , 28 ]. It is further confirmed by our study that AKG as a precursor for the biosynthesis of glutamate and glutamine, inproved the secretion and expression of inflammatory cytokines in response to LPS stimulation, thereby increasing intestinal immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding protein band was thereafter subjected to LC-MS/MS assay. After elimination of false-positives presenting in controls, this protein was identified as PXR, a key regulator of the detoxification of xeno- and endobiotics 23 (Fig. 4a ).…”
Section: Resultsmentioning
confidence: 99%